The SAGE dictionary of qualitative management research - Thorpe, Richard, 1951-; Holt, Robin, 1966- (SAGE, 2008)
With over 100 entries on key concepts and theorists, this dictionary of qualitative management research provides full coverage of the field, explaining fundamental concepts and introducing new and unfamiliar terms.